2004
DOI: 10.1177/153537020422900911
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Patterns in the Daily Weight Chart at Night Predict Body Weight Regain

Abstract: This study examined whether charting daily weight patterns can predict weight regain in obese patients. The subjects were 98 moderately obese Japanese women aged 23 to 66 years who were obliged to precisely record their daily weights during the initial 4-month education period, but not thereafter. The patients were followed up at 8, 12, and 16 months. Abdominal fat areas and blood samples were assessed in the outpatient clinic at 0, 4, and 16 months. The standard deviations (SDs) of the differences in body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…With the exception of one study that exclusively recruited males [ 31 ], all other study samples primarily included middle-aged females. Four studies recruited females exclusively [ 24 , 25 , 27 , 33 ] and two studies were conducted in Japan [ 33 , 34 ]. Median baseline body mass index (BMI) was about 30 kg/m 2 across all samples (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of one study that exclusively recruited males [ 31 ], all other study samples primarily included middle-aged females. Four studies recruited females exclusively [ 24 , 25 , 27 , 33 ] and two studies were conducted in Japan [ 33 , 34 ]. Median baseline body mass index (BMI) was about 30 kg/m 2 across all samples (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al [ 24 ] found that, compared to participants who did not lost 5 kg or more, participants who lost 5 kg or more in a behavioral weight loss program significantly increased their daily self-weighing frequency between baseline and 6-months follow-up. An uncontrolled cohort study by Tanaka and colleagues [ 33 ] found that participants who completed a nutrition-focused weight loss program whereby they self-weighed 4 times per day lost a significant amount of weight (~4 kg) over 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total existing English language articles related to self‐weighing, only 16 met our inclusion criteria. Of the 16 articles, we further excluded 3 RCTs, because self‐weighing was not included among the weight loss intervention strategies , self‐weighing was not used for weight management but only for recording weight , and the effects of self‐weighing on outcomes were not evaluated . On the basis of the remaining 13 RCTs, we further identified 4 relevant studies using the Cited Reference Search strategy, bringing our total to 17 studies.…”
Section: Methodsmentioning
confidence: 99%
“…Higher fluctuation in weight may signal less consistency in weight control behaviors. 5 However, research regarding the benefit of short-term weight consistency is mixed. On the one hand, Orsama and colleagues 6 found higher weights on weekends than weekdays, a pattern that was strongest in those who lost or maintained, rather than gained, weight over time.…”
Section: Introductionmentioning
confidence: 99%